AWARENESS DURING COVID-19: AN ANALYSIS OF CELEBRITY ENDORSEMENT ON SOCIAL MEDIA - Ms. Shweta Chugh, Ms. Sarima Thakur (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today celebrities are not just the entertainers who just entertain the public with the acting and style. But they are the part of the public now, who enjoy public recognition by using social media platforms for interacting with large numbers of followers. For an audience a celebrity can be film actors , sports person or others famous personality of a particular . Social media platforms also show news feeds about celebrities contributing towards the good cause. And celebrities also share their videos or messages on social media platforms, so fans should also follow them and contribute towards the noble cause. Celebrities massages, activities can have the power to impact a large number of people. Followers of a particular celebrity consider them as an opinion leader. This research paper explores the impact of celebrity endorsement in public awareness campaigns (focusing on Covid 19 coronavirus).